1995
DOI: 10.1089/aid.1995.11.327
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1-Neutralizing Antibodies Raised to a Glycoprotein 41 Peptide Expressed on the Surface of a Plant Virus

Abstract: An oligonucleotide encoding the amino acids 731-752 of the gp41 envelope protein of the human immunodeficiency virus type 1 strain IIIB, which is known to induce cross-reactive neutralizing antibodies in humans, was inserted into a full-length clone of the RNA encoding the coat proteins of cowpea mosaic virus (RNA 2 of CPMV). When transfected together with RNA 1 of CPMV, transcribed RNA 2 was able to replicate in plants and form infectious virions (CPMV-HIV). Purified virions were injected subcutaneously with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 43 publications
1
52
0
1
Order By: Relevance
“…In contradiction to this classical model, several studies have described antibodies strongly reacting with a region situated C terminally to the membrane-spanning domain, thought to be located within the cell, in serum samples of HIV-infected patients (6,10,23,30,59). Furthermore, some groups have reported that antibodies against this region are able to modestly neutralize some strains of HIV type 1 (HIV-1) and HIV-2 under modified conditions in vitro (3,9,15,19,25,35,36).…”
mentioning
confidence: 98%
“…In contradiction to this classical model, several studies have described antibodies strongly reacting with a region situated C terminally to the membrane-spanning domain, thought to be located within the cell, in serum samples of HIV-infected patients (6,10,23,30,59). Furthermore, some groups have reported that antibodies against this region are able to modestly neutralize some strains of HIV type 1 (HIV-1) and HIV-2 under modified conditions in vitro (3,9,15,19,25,35,36).…”
mentioning
confidence: 98%
“…Consequently, several HIV antigens have already been expressed in plants, the most common being the envelope protein (Env), alone or in combination (17,25,27,31,39,40). Two groups have expressed a full-length Tat, but in one case, using potato, they did not report immunogenicity studies (19), and in the other case, using spinach (18), oral immunization with plant-based Tat did not induce antibody production.…”
mentioning
confidence: 99%
“…Increasing knowledge of the molecular biology of plant viruses has raised the possibility of using these viruses as antigen expression systems (1)(2)(3)(4)(5)(6)(7)(8)(9). Unlike conventional recombinant vaccines, which are largely derived from live-recombinant, live-attenuated, or killed pathogens (10)(11)(12)(13)(14), plant viruses are generally recognized to be nonpathogenic in humans and other animals.…”
mentioning
confidence: 99%
“…Thus, interest in plant viruses as a system for the expression and delivery of antigens is growing. Tobacco mosaic virus (TMV), cowpea mosaic virus, and tomato bushy stunt virus have been successfully used to express antigenic determinants from different human or animal pathogens (1)(2)(3)(4)(5)(6)(7)(8)(9). We have adapted alfalfa mosaic virus (AIMV) coat protein (CP) to express foreign peptides and have demonstrated that mice immunized with such engineered virus produce antibodies specific for the target antigen (7).…”
mentioning
confidence: 99%